Canadian Inuit subsistence: Antinomies of the mixed economy. Issue 4 (April 2019) - Wenzel, George W
Abstract : From the advent of the fur trade in the Canadian Arctic to the present, it has been repeatedly predicted that the cumulative effect of Euro-Canadian and, more recently, globalised sociocultural and economic pressures would transform the traditional Inuit economy from a system of socially instituted and organised cooperative food production into one in which labour is individualised and commodified. Instead, contemporary Nunavummiut subsistence culture has evolved into what is best described as a mixed economy adaptation with two intertwined sectors: one still based in the production, distribution and consumption of socially valued traditional resources (the 'informal' sector) and the other in which money is a scarce, but critical, resource and the externally recognised standard of valuation (the 'formal' sector). Further, this adaptation functions through the variable articulation of these sectors' respective currencies (traditional foods and externally-sourced money). This hybridisation is a response to contemporary Inuit reality in which wild foods are vital to Inuit physical and cultural health, while money is essential to acquire and maintain the technologies needed to conduct traditional resource activities. While the adaptive effectiveness of the Inuit mixed economy has been repeatedly demonstrated, it is also the case that certain antinomies regarding the extent of harmony between its sectors have sometimes been glossed over, if not overlooked outright. This paper will examine inherent tensions occurring between the material provisioning and social maintenance aspects of this economic adaptation as a component of contemporary Inuit subsistence culture.